Web-based health information seeking: A small-scale comparative study between Finnish and South African university students. Issue 4 (18th November 2019) - Rantala, Annika; Enwald, Heidi; Zinn, Sandy
Abstract : Purpose: The purpose of this paper is to examine differences of health information seeking among Finnish and South African university students. The focus is on weight management and on how students utilise various internet sources. Design/methodology/approach: Data were collected with a web-based, structured survey by using convenience sampling. Descriptive statistics and Pearson's χ 2 test were utilised in the analysis. Findings: Overall, health information was more often encountered than sought on purpose. Passive information seeking was more common for South African students as almost a third of them report encountering it several times a week. As an information source, South African students opted for social networking sites more frequently than search engines, the latter being the first choice for Finnish students. Discussion boards were more popular among South African students, and, on the other hand, web-based health calculators among Finns. Research limitations/implications: This is a small-scale comparative study. The results are not to be generalised, but may provide clues about the information seeking differences between Finland and South Africa. Practical implications: Media literacy, digital literacy and health information literacy of young adults should be emphasised so that they would be able to evaluate information for reliability and accuracy in order to help them make appropriate decisions when confronted by health information online. Social implications: The implications of the study are that health providers and professionals should be more prominent on social media sites, which are popular ways for young people to discover information. Originality/value: Comparative studies are rare. This comparison is between Finland, where internet penetration is 94 per cent, and South Africa, where internet penetration is 54 per cent.